PENGARUH STRES KERJA DENGAN KINERJA PERAWAT DI RUMAH SAKIT - Fayola Issalillah (Jurnal Ilmiah Satyagraha, 2022)
The need for nursing personnel is increasing with the ability to workand demands the best quality of service. Various pressures and workloadsmake it possible to create work stress conditions for nurses in hospitals andaffect their performance to provide patient care. The purpose of the study inthis article is to analyze and determine the relationship between work stressconditions and the performance of nurses in health services in hospitals. Thisarticle used systematic review with a meta-analysis of suitable articles fromGoogle Scholar. Meta-analysis results from 10 selected journals shows thatthe correlation of the medium effect size between job stress and nurseperformance was r = -0.37 (95% CI = (-0.499, -0.219) from the random effectsize based on = 87.3%. Job stress affect nurse performance at medium leveland negative way which lower the stress of job, the higher the nurse'sperformance in providing services at the hospital.